Experimental assessment of the state of the lining materials used in the rehabilitation of sewers in residential buildings. (December 2019) - Kharazmi, Parastou
Abstract: The global needs associated with aging sewers in infrastructures are immense; moreover, traditional renewal by replacement is very costly and not fast enough to meet the renewal needs. To keep up with the rate of deterioration, different rehabilitation technologies, such as the use of polymeric lining, have seen increasing use worldwide. Pipe lining is a solution to stabilize the deterioration of the host pipes in order to extend the service life of the piping system. However, the properties of polymeric materials may degrade over time; therefore, the long-term performance of these lined pipes is a frequently raised concern in the field. The aim of this study was to investigate the state of sewers that had been previously renewed, in order to gather information that facilitates an understanding of the changes in properties of the lining materials after installation. Moreover, to identify the general issues related to pipeline rehabilitation with polymeric systems. The samples investigated in this work had three different types of linings, service times ranging from one week to ten years, were installed by five separate installation companies and had been removed from residential buildings located in different parts of Sweden. The state of the polymeric lining and the relined samples were studied by means of tests including microscopy and visual inspection, as well as thermal analysis such as dynamic mechanical analysis (DMA) and differential scanning calorimetry (DSC), mechanical testing, such as tensile and flexural testing, and thickness measurements.